2023
DOI: 10.7150/jca.79593
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic MicroRNA Fingerprints Predict Recurrence of Early-Stage Hepatocellular Carcinoma Following Hepatectomy

Abstract: Purpose: This study aims to develop liquid biopsy assays for early HCC diagnosis and prognosis. Methods: Twenty-three microRNAs were first consolidated as a panel (HCCseek-23 panel) based on their reported functions in HCC development. Serum samples were collected from 103 early-stage HCC patients before and after hepatectomy. Quantitative PCR and machine learning random forest models were applied to develop diagnostic and prognostic models. Results: For HCC diagnosis, HCCseek-23 panel demonstrated 81% sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 57 publications
0
0
0
Order By: Relevance
“…For patients with hepatitis B virus-related HCC who undergo LR, Cho et al [ 98 ] support circulating levels of miR-26a and miR-29a as predictors of poor DFS and OS. Recently, Wong et al [ 10 ] combined quantitative PCR and artificial intelligence to integrate circulating microRNA with laboratory tumor characteristics and create a diagnostic and predictive model of DFS in patients undergoing LR. These authors identified a panel of eight microRNAs (which they termed the HCC seek-8 panel) that, in combination with serum biomarkers, was significantly associated with DFS.…”
Section: Other Markersmentioning
confidence: 99%
See 1 more Smart Citation
“…For patients with hepatitis B virus-related HCC who undergo LR, Cho et al [ 98 ] support circulating levels of miR-26a and miR-29a as predictors of poor DFS and OS. Recently, Wong et al [ 10 ] combined quantitative PCR and artificial intelligence to integrate circulating microRNA with laboratory tumor characteristics and create a diagnostic and predictive model of DFS in patients undergoing LR. These authors identified a panel of eight microRNAs (which they termed the HCC seek-8 panel) that, in combination with serum biomarkers, was significantly associated with DFS.…”
Section: Other Markersmentioning
confidence: 99%
“…Specifically, three categories of markers have been identified: (i) markers measured in liquid biopsy specimens, (ii) gene signatures, and (iii) markers associated with inflammation. A few markers not in any of these categories have also been identified, including prothrombin induced by vitamin K absence-II (PIVKA-II), programmed cell death protein-1 (PD-1), microRNAs, and proteins in urinary exosomes (Figure 1) [8][9][10][11]. Unfortunately, not all of the aforementioned markers are readily available in clinical practice, and their reproducibility is unclear.…”
Section: Introductionmentioning
confidence: 99%